Operational Research Framework of Open Innovation Business Model Strategic Plan for Malaysian Small Medium Business Enterprise in Software Industry - Soffri Yussof; Mohd Naz'ri Mahrin; Aini Suzana Ariffin (Penerbit UTM, 2022)
Malaysian Small and Medium Enterprises (SMEs) are the critical factors of the nation's economic growth. Limited studies on their systematic strategy on aligning the business model innovation (BMI) into the inbound open innovation (IOI) spectrum were examined. Therefore, the focus of this study is to access necessitate IOI and BMI strategies that can contribute to a systematic strategy. As a result, the primary purpose of this study is to present the entire operational framework that will be utilised to formulate the Strategic Plan inclusive of the IOI and BMI strategies. The operational research framework consists of four phases, Phase 1: Systematic Literature Review, Phase 2: Semi-structured interview, Phase 3: Formulation of Open Innovation Business Model Strategic Plan (OIBM-SP), and Phase 4: Evaluation OIBM-SP. The result of this study is the formulation of OIBM-SP for Malaysian SMEs in the software industry.